Influence of Rail Line Gradient and Curve on Pantograph-Catenary Dynamic Performance - Huan ZOU; Ning ZHOU; Dong ZOU; Weihua ZHANG (机车电传动)
In the study of the key mechanics problems in high-speed train, the pantograph-catenary dynamic performance under rail line gradient and curve is one of the most important research contents. The finite element technique and multi-body dynamics theory were adopted, a whole space vehicle-pantograph-catenary coupling system simulation platform was built, and then, the dynamic response of the model runs on vertical curve track, constant slope track, horizontal curve track were calculated and studied. The results showed that, when the slope change rate is 0, the influence of line on the dynamic response of the pantograph/catenary isn’t obvious;the positive slope change rate of the contact wire decreases the mechanical wear of pantograph/catenary, the stability of current is reduced, and it increases the electrical wear, but the negative slope change rate of the contact wire makes opposite; the smaller the radius of the vertical and horizontal curve, the worse the stability of the pantograph/catenary dynamic performance, which can not be ignored in the simulation, and it should be considered in the line design, construction and interval speed limit of horizontal curve and vertical curve setting.